2022
DOI: 10.1002/acr.25015
|View full text |Cite
|
Sign up to set email alerts
|

Association of Area‐Level Heat and Social Vulnerability With Recurrent Hospitalizations Among Individuals With Rheumatic Conditions

Abstract: Objective Climate and social vulnerability contribute to morbidity and health care utilization. We examined associations between the neighborhood Social Vulnerability Index (SVI) and the Heat Vulnerability Index (HVI) and recurrent hospitalizations among individuals with rheumatic conditions. Methods Using a Massachusetts multihospital centralized clinical data repository, we identified individuals ≥18 years of age with a rheumatic condition who received rheumatology care within 3 years of April 2021. We defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Limitations of this study include lack of data outside of our population cohort, as we have only analyzed individuals enrolled in the iCMP program who may be more likely to both have higher prevalence and documentation of SDoH‐related needs compared to a less complex population. Compared to a prior study in individuals receiving rheumatic disease care within our multihospital system (6), this population, on average, was about 10 years older, had a similar gender and race distribution, and had a higher percentage of Hispanic individuals and Medicare beneficiaries. As iCMP only requires the primary care physician to be within the multihospital system and not the subspecialists, there may be misclassification of rheumatic/musculoskeletal conditions.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Limitations of this study include lack of data outside of our population cohort, as we have only analyzed individuals enrolled in the iCMP program who may be more likely to both have higher prevalence and documentation of SDoH‐related needs compared to a less complex population. Compared to a prior study in individuals receiving rheumatic disease care within our multihospital system (6), this population, on average, was about 10 years older, had a similar gender and race distribution, and had a higher percentage of Hispanic individuals and Medicare beneficiaries. As iCMP only requires the primary care physician to be within the multihospital system and not the subspecialists, there may be misclassification of rheumatic/musculoskeletal conditions.…”
Section: Discussionmentioning
confidence: 74%
“…A study of patients with systemic lupus erythematous (SLE) showed that moving out of poverty led to lower mean scores of newly accumulated disease damage, similar to scores of participants who were never in poverty (5). Across rheumatic conditions, living in areas of high heat or social vulnerability has been associated with higher odds of recurrent hospitalizations (6).…”
Section: Introductionmentioning
confidence: 99%